Frequency of Bioprosthetic Valve Fracturing Utilization in an All-Comers Valve-in-Valve TAVR Cohort - Ruge, Hendrik; Erlebach, Magdalena; Lange, Ruediger (Frontiers in Cardiovascular Medicine, 2021)
Introduction Valve-in-valve TAVR (ViV-TAVR) is an established treatment for failing surgical aortic valves in patient at high surgical risk. Elevated transprosthetic gradients are common after ViV-TAVR. Previously, bench tests showed feasibility of bioprosthetic valve fracturing (VF) using high-pressure balloons. Small case series show reduced transprosthetic gradients using VF. We present our clinical experience and outcome of VF. Material and Methods Consecutive ViV-TAVR patients were identified from our institutional TAVR database and utilization of bioprosthetic valve fracturing or intraprocedural postdilatation was reviewed. Surgical valves were categorized as responsive or not responsive to VF. Transprosthetic gradients were compared in procedures with VF and procedures with or without postdilatation. Results In 67 consecutive ViV-TAVR procedures between January 2018 and September 2020, VF was attempted in 15 cases with eight being successful. Standard postdilatation was performed in 21 patients and 31 cases were without postdilatation. Mean transprosthetic gradients (MPG) decreased from 34.2+12.5mmHg to 12.7+7.4mmHg (p<0.001) for all patients. MPG was 8.6+3.5mmHg after VF, 12.9+8.5mmHg after standard postdilatation (p=0.18) and 13.4+6.8mmHg in cases without postdilatation (p=0.04). In small surgical valves with true inner diameter < 21mm MPG was 9.1+3.5 mmHg after VF, 14.2+8.9 after standard postdilatation (p=0.068) and 16.2+9.2mmHg without postdilatation (p=0.152). Failed attempts with BVF occurred with the Perimount standard valve. Conclusion Bioprosthetic valve fracturing results in lower mean transprosthetic gradients after ViV-TAVR. Responsiveness of BVF in Perimount surgical valves, long-term hemodynamic outcome and potential survival benefits need further evaluation